RESULTS OF NEGATIVE PRESSURE WOUND THERAPY IN INFECTED SURGICAL WOUND AT THE DIGESTIVE SURGERY DEPARTMENT, VIET DUC UNIVERSITY HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Taking care of infected surgical wounds helps patients quickly heal the surgical wound and to reducethe time to treatment.Aims: Evaluate the results of care for infected surgical wounds by Negative pressure wound therapy.Patients and methods: 30 patients with infected surgical wounds were cared for by Negativepressure wound therapy at the Department of digestive surgery, Viet Duc university hospital, from3/2020 to 7/2021.Results: The rate of superficial infection was 66,7%, and the rate of deep infection was 33,3%.The rate of clean surgery was 3,3%, clean-contaminated surgery was 60,0%, contaminated surgerywas 33,3%, and infected surgery was 3,3%. In 30 patients with infected surgical wounds treatedby Negative pressure wound therapy: 4 days (93.3%), 8 days (6.7%). The results of taking care ofinfected surgical wounds: 76,7% of patients were recovered and discharged from the hospital, 23,3%of patients had a reduction of wound infection and were transferred to a local hospital, the averagetime of hospitalization after surgery was 11,7 ± 3,9 days.Conclusions: The technics of care for infected surgical wounds by Negative pressure wound therapyare feasible and effective in treating surgical wound infection.
Keywords: Wound infection, negative pressure wound therapy.